Mother's Knowledge of Efforts to Prevent Covid 19 Transmission in Children Age 3 - 5 Years Old - Dwi Ertiana; Sri Utami (JURNAL KESEHATAN POLTEKKES KEMENKES RI PANGKALPINANG, 2022)
Background: The Covid-19 pandemic that has spread worldwide threatens all groups, including children. Health protocols were quickly implemented to break the chain of the spread of Covid-19. The mother's role is crucial in taking extra precautions for safety against COVID-19, especially for children aged 3-5 years.Objective: The purpose of the study was to analyze mothers' knowledge about efforts to prevent transmission of covid 19 in children aged 3 - 5 years.Method: This is descriptive research. The research variable is the mother's knowledge about efforts to prevent the transmission of covid 19 in children aged 3-5 years. The study was carried out in Asmorobangun Village, Puncu Health Center, Kediri Regency, on July 5 - August 5, 2021. The study population was 228 mothers. Using the Proportional Random Sampling technique, a sample of 213 mothers was obtained. They collected data using a questionnaire.Result: The knowledge of respondents who have children aged 3-5 years is good as many as 179 people (84%), 28 respondents (13.1%) respondents have sufficient knowledge and 6 respondents (2.8%) have less knowledge.Conclusion: Information that mothers receive through various public service advertisements in various media can encourage mothers to memorize the information provided, provide the benefit of increasing mothers' knowledge in terms of preventing transmission of the coronavirus, especially to children, so that mothers can use it in carrying out coronavirus prevention behaviours properly and avoiding members families, especially children from exposure to the coronavirus.